-5c-9d/3c+5c-d/6c

Simple and best practice solution for -5c-9d/3c+5c-d/6c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5c-9d/3c+5c-d/6c equation:


x in (-oo:+oo)

5*c-5*c-(c*((9*d)/3))-(c*(d/6)) = 0

5*c-5*c-3*c*d-(c*(d/6)) = 0

-19/6*c*d = 0

x naleu017Cy do R

x in (-oo:+oo)

See similar equations:

| 16d+1=7d+55 | | -6(5y+4)+6y=144 | | X^2-8x+18=6 | | 6(x-8)=-19.2 | | -6(5y+4)+6y=14y | | 3(a+4)=21.3 | | 3x-18=-66 | | 11x-6x=20-8x | | 67.3=9c-2 | | 6e-5=16 | | 6e-5=15 | | -4.8x=-13.92 | | 2p=9.6 | | 9(8x-4)=30 | | 9(a+5)=63 | | 5(2x-1)=27 | | 7e-9=54 | | 9p=81 | | 9y^2-16x^2=144 | | 13x^2+65x=0 | | 16x^2+7y^2=448 | | 13x^2+65=0 | | 2p+3q= | | 22/3x11/3x31/6 | | g/4+b/2=21 | | 9x^2-30x+-25=0 | | 5x+2y-1=0 | | 66=-2(4y+3) | | 5x+2y-1=9 | | 1.2x+2.3=3.4 | | 3rs-5r+s-4rs+12r-s= | | 4+x=-3x |

Equations solver categories